Prospects for renewable energy sources from biomass waste in Indonesia - Erdiwansyah, E.; Gani, Asri; Rizalman, Mamat; Bahagia; Nizar, Muhammad; Yana, Syaifuddin; Mohd Hafizil, Mat Yasin; Muhibbuddin, M.; S. M., Rosdi
This research evaluates energy dependence and dependence on fossil fuels. Indonesia's abundant renewable energy sources can be used as an environmentally friendly and sustainable energy alternative. The potential for renewable energy in Indonesia reaches 3687 GW (GW), but only 12,736.6 MW (MW) have been utilized. The highest energy potential was found from solar energy, reaching 3294 GW; wind energy, 155 GW; hydropower, 95 GW; and marine energy, 63 GW. Meanwhile, palm oil mill solid waste has a high calorific value, so it is suitable for use as raw material for energy production.